A cross-sectional study of evidence-based practice and its determinants among healthcare professionals in Northwest Ethiopia - Melkamu, Yideg; Asemahagn, Mulusew Andualem; Walle, Ayinengida Adamu; Tsega, Yawkal (Frontiers in Medicine, 2024)
Background: Evidence-based practice (EBP) is the integration of current best evidence with clinical expertise by considering patient preferences and values. Evidence based practice has not been well studied in Ethiopia. Therefore, this study aimed to assess EBP and its determinants among health professionals working at primary hospitals in Central Gondar zone public hospitals, Northwest Ethiopia.A facility-based cross-sectional study was conducted on 422 health professionals. A simple random sampling technique was used to select the study participants. The data were entered into EpiData version 4.6 and exported to SPSS version 25 for analysis. The descriptive, bivariable, and multivariable logistic regression analysis were conducted. Adjusted Odds Ratio (AOR) with 95% confidence intervals and p-value <0.05 was used to assess association of explanatory variables with EBP and declare statistical significance, respectively.Result: About 44.1% (95%CI: 39, 50%) of healthcare professionals had good evidence-based